The Effects of MicroRNAs on Key Signalling Pathways and Epigenetic Modification in Fibroblast-Like Synoviocytes of Rheumatoid Arthritis - Wenming Hong; Pengying Zhang; Xinming Wang; Jiajie Tu; Wei Wei (Mediators of Inflammation)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression at the posttranscriptional level via direct binding to the 3′-untranslated region (UTR) of target mRNAs. Emerging evidence shows that miRNAs play crucial roles in controlling and modulating immune system-related diseases. This review focuses on the role played by miRNAs in fibroblast-like synoviocytes (FLS), which is a key cellular component within synovia, during the establishment and maintenance of rheumatoid arthritis (RA), a systemic inflammatory autoimmune disease. It also provides an overview and classification of known functional miRNAs in RA FLS and summarizes the potential uses of these small molecules in RA diagnosis and treatment.